The Optimization of Budget Absorption in the Use of General Allocation Funds (DAU) for the Health Sector in Bengkalis Regency - Hafizhah Maulia; Ermanto; Jasrida Yunita (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
This study aims to identify and analyze the factors influencing the low absorption rate of the General Allocation Fund (DAU) for the health sector by the Bengkalis Regency Health Office in 2024. The research employed a qualitative approach using data collection methods such as direct observation, interviews, and document analysis. Data were analyzed using a Fishbone diagram to identify root causes, the USG (Urgency, Seriousness, Growth) method to determine problem priorities, and the Delphi method to formulate solutions. The findings revealed that by the third quarter of 2024, DAU absorption was only 58%, far below the target. The main issues included poor inter-sectoral coordination, administrative delays, and limited human resource capacity. Proposed strategies include developing SOPs, establishing cross-sectoral teams, and implementing technology-based monitoring systems to enhance efficiency, transparency, and accountability. This study provides practical recommendations for optimizing DAU absorption to support better public health services.